(untitled) (Scientific journal of the Fergana State University, 2024)
Globally, satisfying the population’s demand for meat products is considered one of the most urgent tasks. Based on this, reforms are being carried out in our Republic to develop animal husbandry, especially fisheries. But one of the factors seriously hindering high productivity from fish is parasites. Helminths occupy the main place among the parasites of fish. It follows that it is important to use anthelmintic drugs against disease-causing helminths in fish. The study characterised the plerocercaria larvae of the causative agent of the disease Ligulidosis, the cestode Ligula intestinalis. In a trial of anthelmintic drugs against fish parasites. Anthelmintic drugs mebendazole (10 %), fenmendazole (22 %) and Alben (20 %) were used to determine the biological efficacy of the drugs against gastrointestinal cestodoses of white-fleshed silverfish.